Modifiable factors associated with cognitive health trajectories among Indigenous, Hispanic, Black, and White older adults: an exploratory longitudinal panel analysis of the health and retirement study with a focus on Indigenous peoplesResearch in context - Cliff Whetung; Ernest Gonzales (The Lancet Regional Health. Americas)
Summary: Background: Despite elevated dementia risk, cognitive health among Indigenous older adults remains understudied. This study explored how modifiable factors were associated with cognitive health among Indigenous, Black, Hispanic, and White older adults. Methods: Using longitudinal panel data from the Health and Retirement Study (2006–2020, N = 27,327), we estimated mixed effect growth curve models to examine associations between modifiable factors and total cognitive function. Findings: This diverse sample of Indigenous (1.65%), Black (11.43%), Hispanic (9.85%), and White (77.07%) older adults had a mean age of 61 (SD = 9.66) and was 52% female. Despite being younger on average (M = 59), 3% of Indigenous respondents reported memory-related diagnoses three times the overall sample rate. Linear mixed-effect growth curve analysis revealed that Indigenous and Black older adults had similar cognitive trajectories. A college education was a protective factor for initial cognitive function (b0 = 3.09, 95% CI: 2.91, 3.27) and over time (b = 0.24, 95% CI: 0.15, 0.33) across ethnicity. Formal (b = 0.21, 95% CI: 0.15, 0.27) and informal (b = 0.26, 95% CI: 0.20, 0.32) volunteering were associated with slower rates of cognitive decline relative to non-volunteers, though these effects may partly reflect socioeconomic status. Among Indigenous older adults, higher education, volunteering, and fewer depressive symptoms were linked to better cognitive outcomes. Interpretation: Despite high levels of resource deprivation, Indigenous older adults demonstrate resilience that supports cognitive health. Expanding access to education and volunteering in later life through targeted social policy may enhance cognitive outcomes in Indigenous communities for generations. Funding: This research was supported by the National Institute on Aging (R36AG078781).